DETERMINANTS OF SUSTAINABILITY OF RURAL COMMUNITY BASED WATER PROJECTS IN NAROK COUNTY, KENYA - Achieno, Godfrey Osborn; Mwangangi, Dr. Patrick (International Journal of Entrepreneurship and Project Management, 2018)
Purpose: The purpose of this study was to determine the factors influencing sustainability of rural community based water projects in Narok County, Kenya. Methodology: The study employed descriptive survey with a target population of 163 and sample size of 85 respondents selected randomly from 15 community based water facilities. The study used closed ended questionnaires. Pilot study results were used to test reliability and validity of the instruments found. Data was analysed using descriptive statistics and inferential analysis by use of Statistical Package for Social Sciences (SPSS) version 21 and presented using frequency distribution, percentages, mean, standard deviation and Pearson Product Moment Coefficients (PPMC). Results: The correlation results revealed that community participation and project management practices have a positive and significant relationship with sustainability among rural community based water projects while technology use and post implementation support had a low relationship with sustainability of rural community based water projects. Unique contribution to theory, practice and policy: The community members should be adequately involved in identification, planning, implementation and close out phases of water projects. There should be regular participatory meetings with stakeholders, empowerment workshops for community members, trainings for water management committees, joint meetings on establishing mechanisms for protection of water facilities and conflict resolution. Keywords: Community participation, project management practices, technology, post implementation support, sustainability